Alat Pendeteksi Level Air Otomatis Pada Tangki Air Wudhu Masjid Ulil Albab UNSRAT Berbasis Mikrokontroller - Rendy Syahputra (Jurnal Informatika, 2023)
The era of globalization as it is today, the development of technology is growing so rapidly.However, this is not coupled with the technology in the water storage tank in the mosque that still uses manual water measurement, which results in the end of wudu water without realizing it so that the congregation has difficulty wudu water. After seeing the problem, then designed a tool to determine the water level in the water tank that can determine the amount of water volume in the water storage tank and can provide a warning in the form of an alarm. The results of testing the water level detector on the ablution water storage tank at ulil albab mosque based on this microcontroller are able to work well, this water measurement uses ultrasonic sensors. and is able to display the indicator of the amount of water volume, then the buzzer will sound when the water in the storage tankimmediately runs out.